Pemetaan Wisata Kuliner Khas Kota Surakarta - Amad Saeroji; Deria Adi Wijaya (Jurnal Pariwisata Terapan, 2017)
This article discusses the mapping of specific cuisines as culinary tourism potential in Surakarta. The general objective is to present a culinary-mapping of specific culinary products where the information can be used by stakeholders such as goverment, culinary business, travel industries, including tourists. The implementation of the study has specific objectives: (1) identify the specific culinary potentials in Surakarta, (2) create a culinary tourism map in Surakarta City. This research applies descriptive-qualitative research methods in the effort of apprising the information of unique/specific culinary tourism in Surakarta. Data collection techniques wae conducted through participatory observation, in-depth interviews and literature studies. The data collection through observation and interviews were conducted in government agencies, travel industries and culinary tourism businesses around Surakarta. The literature study included all concepts and theories related to culinary tourism especially culinary references in Surakarta. The results obtained from this study indicate that the potential of culinary tourism in Surakarta is very diverse with each peculiar identity. In connection with a variety of culinary potential is then presented on the Surakarta culinary map which helps stakeholders in developing Surakarta’s culinary tourism.